2017
DOI: 10.1159/000477112
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Attenuates Ventilation Induced Lung Injury via SIRT1-Dependent Inhibition of NLRP3 Inflammasome

Abstract: Background: Salidroside (SDS) is the main effective ingredient of Rhodiola rosea L with a variety of pharmacologic properties. We aim to investigate the effects of SDS on ventilation induced lung injury (VILI) and explore the possible underlying molecular mechanism. Methods: Lung injury was induced in male ICR mice via mechanical ventilation (30 ml/kg) for 4h. The mice were divided in four groups:(1) Control group; (2) Ventilation group; (3) SDS group; (4) Ventilation with SDS group. SDS (50 mg/kg) was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 57 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…In addition, SIRT1 is closely related to the activation of NLRP3 inflammasome . In rat cerebral ischaemia/reperfusion models and ventilation‐induced lung injury models, SIRT1‐dependent inhibition of NLRP3 inflammatory body activation . Therefore, it may be assumed that quercetin effects on DM in db/db mice through SIRT1/NLRP3 signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SIRT1 is closely related to the activation of NLRP3 inflammasome . In rat cerebral ischaemia/reperfusion models and ventilation‐induced lung injury models, SIRT1‐dependent inhibition of NLRP3 inflammatory body activation . Therefore, it may be assumed that quercetin effects on DM in db/db mice through SIRT1/NLRP3 signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, the NLRP3 inflammasome exhibits a significant initiating mechanism, and its activation may accelerate the development of endothelial dysfunction or atherogenic pathology by inducing plasma trimethylamine-Noxide (TMAO) [38]. The repression of the NLRP3 inflammasome is a critical factor in I/R or inflammation by correlation with SIRT1, which was proved to be involved in both preventing cells from injury induced by various stress and improving endothelial precursor cell function [39,40]. Activating the NLRP3 inflammasome signaling can promote atherosclerosis pathogenesis via the overexpression of inducible endothelial-specific GPR124 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside also exerted its anti-inflammatory effect by inhibiting the production of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6) through the blocking of the NF-κB and MAPK signaling pathways both in vitro in RAW 264.7 macrophages and in vivo in mice challenged with lipopolysaccharide [134, 135]. Further studies revealed that salidroside inhibited the activation of NLRP3 inflammasome and subsequent caspase-1 cleavage as well as IL-1β secretion both in vivo and in vitro through up-regulation of SIRT1 expression [136]. In addition, salidroside can inhibit the JAK2-STAT3 pathway by suppressing nuclear localization of STAT3 [137].…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%